2024
DOI: 10.2478/ats-2024-0001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary olive‑garlic extract oil supplementation: influence on performance and haematological indices of broilers

Gabriel Adedotun Williams,
Adetutu Victoria Babatunde,
Fatimah Damilola Bello
et al.

Abstract: The use of antibiotic growth promoters in broiler production has been the norm in developing countries, however, the increased rate of antibiotic resistance in humans has resulted in the search for alternatives without negative residual effects. This study investigated the effect of dietary olive garlic extract oil (OGEO) supplementation on the performance and haematological indices of broilers. The experiment lasted for 42 days and broilers were fed varying levels of OGEO‑supplemented diets at the starter (0–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Additionally, a study by Cheng et al (50) indicated that Chinese herbs improved immunity in broilers by promoting IgG synthesis in the serum. Furthermore, a study by reference (58) reported that the addition of 1% olive leaf extract significantly improved IgG in broilers. A possible explanation for the positive effects of medicinal plants on IgG may be associated with their role in reducing excessive pro-inflammatory cytokines (IL-8) to maintain a balanced cytokine environment by restoring the integrity of the gut epithelium after HS.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, a study by Cheng et al (50) indicated that Chinese herbs improved immunity in broilers by promoting IgG synthesis in the serum. Furthermore, a study by reference (58) reported that the addition of 1% olive leaf extract significantly improved IgG in broilers. A possible explanation for the positive effects of medicinal plants on IgG may be associated with their role in reducing excessive pro-inflammatory cytokines (IL-8) to maintain a balanced cytokine environment by restoring the integrity of the gut epithelium after HS.…”
Section: Discussionmentioning
confidence: 98%